The Legacies of Slavery in and out of Africa - Graziella Bertocchi (Institute for the Study of Labor (IZA), 2015)
The slave trades out of Africa represent one of the most significant forced migration experiences in history. In this paper I illustrate their long-term consequences. I first consider the influence of the slave trade on the "sending" countries in Africa, with attention to their economic, institutional, demographic, and social implications. Next I evaluate the consequences of the slave trade on the "receiving" countries in the Americas. Here I distinguish between the case of Latin America and that of the United States. For the latter, I further discuss the subsequent migration experiences of the Second Middle Passage, when African slaves were transported, again forcibly, from the coastal regions to the inland, and of the Great Migration, when as free people they chose to leave the deep South for the Northern cities.
Keywords: F22; J15; O15; 330; slavery; Africa; Americas